Les agglomérations de Nyon, Lausanne et Yverdon (Suisse) : trois exemples de l’ouest du plateau suisse entre Antiquité tardive et haut Moyen Âge - Clément Hervé (Gallia)
This contribution gives a first review of archaeological data on Late Antiquity and Early Middle Age of Nyon, Lausanne and Yverdon — three urban areas which illustrate different urban and territorial mutations which occured during those periods in the Western part of the “Plateau suisse”. It is based mainly on recent data which are not entirely analysed and older data which would deserve to be more accurately investigated. Despite these obstacles, results are promising and already enable us to precise and/or nuance many elements. As it has been foreseen for many years, the notion of abandonned sites at the end the Early Roman Empire must be revised. It is particularly the case of the old colony of Nyon-Noviodunum which is not crossed off the map, even if it loses its importance for its neighbour Genève-Genava at the end of the 3rd c. AD. Further to the East on the Lemanic coast, the vicus of Vidy-Lousonna is not also entirely deserted in favor of the site located on the height of the hill of la Cité which will be the new centre of the diocese at the end of the 6th c. On the south bank of the lake of Neuchâtel, Yverdon-Eburodunum, vicus of the Early Roman Empire, where a castrum is put up during the Constantinian time, is without a doubt the site which we knew the best for these periods. However new discoveries enable us to precise the range of this Late-Antiquity city.